STRESS-DEFORMATION ANALYSIS OF THE F16 AIRCRAFT AUXILIARY LANDING GEAR - Yetkin, Seda; Ozmen Koca, Gonca (Yildiz Technical Univ, 2018)
Stress is known as an internal force value acting on a unit area of a part. Stress-deformation analyzes play an important role in finding structural safety and integrity. According to literature, aircraft faults during landing are more frequent than faults during take-off and flight. In this study, the geometry of the auxiliary landing gear of the F16 aircraft is drawn in the SolidWorks package program, which is one of the computer-aided design programs. Later, the finite element analysis is performed on the ANSYS program of the drawing design. Stress and deformation values are determined for each part of the landing gear of F16 aircraft. Two results are obtained by interpreting the stress-deformation analyzes. In the first result, the maximum stress reduces when the shaft diameter in the landing gear is increased. In the second result, the maximum stress and maximum deformation increase when the moment is applied. With these analyzes, endurance tests are carried out by obtaining the stress-deformation values of each part for different shaft sizes of the aircraft landing gear.
Keywords: F16 aircraft; auxiliary landing gear; finite element analysis; stress analysis; deformation analysis